Anti-biofouling materials and surfaces based on mussel-inspired chemistry. Issue 7 (19th March 2021) - Li, Sijia; Chen, Jingsi; Wang, Jingyi; Zeng, Hongbo
Abstract : The mussel-inspired chemistry has been widely applied to fabricate anti-biofouling materials and surfaces through various functionalization strategies. Abstract : Mussel-inspired chemistry has attracted much research interest in manipulating material properties in surface engineering over the past decade due to its universality and versatility. To address biofouling issues, mussel-inspired molecular interaction strategies have provided promising methods for the design and development of anti-biofouling materials that can either repel proteins and microbes to avoid attachment or kill them in the surrounding environment. This review provides an overview of recent advances in mussel-inspired chemistry and its emerging applications in fabricating anti-biofouling platforms. The molecular interactions and adhesion mechanisms of mussel-inspired chemistry are first introduced. The applications of mussel-inspired chemistry in different anti-biofouling hydrogels, membranes and coatings are then discussed. Various bio-inspired material fabrication processes and surface functionalization strategies are presented, in which materials based on the mussel-inspired chemistry play different roles such as surface modifiers, intermediate layers or adhesive moieties to bind other components for functionalizing materials with anti-biofouling performance. Some remaining challenges are discussed, and future perspectives on mussel-inspired modification of anti-biofouling materials are also provided.